Self-care and quality of life among men with chronic heart failure - Wiśnicka, Alicja; Lomper, Katarzyna; Uchmanowicz, Izabella (Frontiers in Public Health, 2022)
Introduction Chronic Heart Failure (CHF) involves a complex regimen of daily self-care behaviors: pharmacological therapy, symptom monitoring and lifestyle modifications. Patients with CHF may have a reduced health related quality of life (HRQoL) due to various physical and emotional symptoms. HRQoL may be improved through the use of self-care interventions. Purpose To assess the level of self-care and quality of life among men with chronic heart failure. Methods The study was conducted among 80 men diagnosed with CHF (mean age 58 years). The study was cross-sectional. A self-administered questionnaire and analysis of medical records were used to collect baseline sociodemographic and clinical data. Self-care was assessed using the standardized European Heart Failure Self-care Behavior Scale- EHFScBS-9 and quality of life was assessed using the World Health Organization Quality of Life Bref. Results The Patients in NYHA class II constituted the vast majority (71.25%), mean LVEF in the study group was 43.5%, and mean disease duration was 3 years. The most common comorbidities were ischemic heart disease (72.5%), hypertension (70%) and diabetes mellitus (60%). The most commonly reported non-pharmacological treatments for NS were fluid restriction (45%), moderate physical activity (42.50%) and daily weight control (41.25%). The EHFSc-9 questionnaire score averaged 50.31 points out of 100 possible (SD = 26.52). The mean score regarding perception of QoL was 2.78 points (SD = 0.91), and 40% of patients indicating poor perception of QoL. The mean score for self-rated Analysis of the results of the individual domains of the WHOQoL BREF questionnaire showed that patients rated their QoL best in the environmental domain (M = 13.28; SD = 3.11), then in the social domain (M = 12.81; SD = 2.71), and in the psychological domain (M = 12.8; SD = 3.2). In contrast, QoL in the physical domain was rated the lowest (M = 10.44; SD = 2.85). There was no significant correlation between quality of life and self-care (p > 0.05). Conclusions Men with CHF have unsatisfactory self-care outcomes and low quality of life scores and are dissatisfied with their health. Strategies to improve selfcare and quality of life in this group are indicated.